The problem of a night of creativity and reception between a thousand and one nights and the play Sarzad by Ali Ahmed Bakathir (Journal of the College of Basic Education, 2022)
Theater is a mass necessity, and a civilized process, and the extent to which this process is trying to be exploredAspects of life on the sociocultural and sociological levels, they are able to open up their horizonsAnd unjustly dissipated. The theater is a ray of light that tries to collect latent beams of light, past and presentAnd then these beams are shed to innovate, create and illuminate new ones